Sublingual cysts of different entities in an infant – A case report and literature review. (October 2018) - Voss, Jan Oliver; Buehling, Salvatore; Thieme, Nadine; Doll, Christian; Hauptmann, Kathrin; Heiland, Max; Adolphs, Nicolai; Raguse, Jan-Dirk
Abstract: Background: Congenital cysts and fistulas of the neck are common in children, often located in the head and neck area. Belonging to the group of tumor-like conditions, dermoid and epidermoid cysts are dysontogenetic lesions with seldom multiple co-occurrences in infants. Case report: We report on a nine-month-old female with a persisting congenital fistula of the tongue. The patient was admitted with acute poor feeding and hypersalivation, which started within the last 24 h. Magnetic resonance imaging detected a fistula of the tongue connected to sublingual cystic lesions. Intraoral surgical removal of three cystic lesions and the fistula was performed under general anesthesia. Histopathological analysis confirmed the coexistence of an epidermoid cyst and two dermoid cysts. Conclusion: Sudden feeding difficulties in combination with dysphagia and tongue displacement in pediatric patients pose an emergency situation that requires prompt diagnostic clarification. A persisting congenital fistula of the tongue is a clear indication of dysontogenetic lesions, including malformations, tumors, and tumor-like lesions. Congenital sublingual cysts are rare in infants, but can be life threatening when present. Surgical excision with histopathological analysis is essential to exclude any form of malignancy and malignant transformation.